The Role of Reactive Oxygen Species and Bacterial Infections in Male in Male Infertility in Al- Anbar Province / West of Iraq - Dhuha A. Abbas; Abbas O. Al.janabi; Waleed N. (Indian Journal of Forensic Medicine & Toxicology, 2021)
In the male genital tract, spermatozoa and leukocytes, including neutrophils and macrophages, generate reactive oxygen species (ROS). ROS is involved in the regulation of sperm functions, such as acrosome reactions and capacitation. Infections result in excessive ROS production, resulting in a ‘oxidative burst’ of neutrophils/macrophages as a first-line defense mechanism. During infection, the imbalance of pro-and antioxidants favoring the former results in oxidative stress that impairs the sperm functions mentioned In addition to motility and fertilization. ROS produced during testis and epididymis infections is especially harmful to sperm due to longer contact time and lack of antioxidant protection. Only very high numbers of ROS-producing leukocytes are harmful to sperm functions in the final ejaculate.